EFEKTIFITAS KOMPRES HANGAT TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF PADA IBU BERSALIN DI BPM ISLAH WAHYUNI PEKANBARU - Linda suryani; Desi Nindya Kirana (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Labor and birth is a physiological process, although the process is physiological, in general it’s scary because it is accompanied by severe pain, sometimes even causing life-threatening physical and mental conditions. Various efforts have been made to overcome labor pain, namely pharmacological and non-pharmacological management. One of non-pharmacological management is hydrotherapy (hot/cold therapy). Warm compress method used in hydrotherapy is more effective and efficient during labor in reducing pain, warm compress stimulates temperature receptors in skin and suppresses pain through gate control theory. This research is a quasi-experimental analytic research with one group pretest posttest design. This research was conducted in September-December 2021 at BPM Islah Wahyuni Pekanbaru. population was all mothers who gave birth to BPM Islah Wahyuni Pekanbaru with total sample of 36 people with accidental sampling technique. analysis used univariate and bivariate data analysis using T-Test Dependent. The results showed scale of labor pain in the first stage of the active phase in women giving birth before warm compresses showed the majority experienced severe pain as many as 17 people (47%) and after warm compresses showed the majority experienced moderate pain as many as 16 people (44%). the t-test obtained p-value 0.000 and t-count (5.431) > t-table (1.688). It can be concluded that warm compress therapy is effective in reducing first stage labor pain in women giving birth. It is hoped midwives can intervene of warm compresses to reduce labor pain because it has been proven to be effective in reducing pain intensity during labor